Control of Oppressive Interest Rates and Charges by Banks and the Relationship between Landlords and Tenants - The Urgent Imperative for Statutory Protection - Babalola (SAN), Afe OFR, CON, SAN, LL.D; Chigbo, Clement C. (Journal of Accounting, 2020)
Purpose: The purpose of the work is to examine the ways by which the court and legislature can control critical interest rates on loan bargains and legislation can be used to exercise/impose a significant legal control over the relationship between landlords and residential/occupiers. Methodology: The paper adopts the doctrinal research methodology/ approach of reviewing cases and statutes and international instruments in aiming at a valid conclusion. Emphasis were placed on statutes and case laws as primary sources. Relevance was as well placed on journal, articles, text books, internet materials, among others as secondary materials. Findings: The paper finds that many Nigerians will be exposed to unmitigated hardship and suffering during this era of covid-19 pandemic as a result of lockdown and restrictions imposed by the government in the effort and measures to contain and curb the spread of the coronavirus. Unique contribution to theory, policy and practice: The paper urges the government to adopt as a primary political objective- the use of legislation to ameliorate the plight of Nigerians in the loan bargain sector and in the residential (housing) sector. In this regard, the paper contributes to practice and policy of government by using law as an instrument of social engineering